Study on properties of dissimilar metal welding between stainless steel (AISI 304L) and mild steel (AISI 1018). / Mohd Soleham Juraimi Kamarudin - Kamarudin, Mohd Soleham Juraimi (2009)
The tensile strength and corrosion resistance of dissimilar metal welds between stainless steel and mild steel have been studied and analyzed. Three different filler metals were used to joint this combination using multi pass, Gas Tungsten Arc Welding (GTAW) process, Dissimilar metal weld were produced by using 3 different types of filler metal le* ER70S-G, ER308L and ER309L. Preliminary Welding Procedure Specification (p-WPS) was prepared for every filler metal used. Defect free welds were produced with each filler metal and inspected with digital radiography technique. The tensile strength of the ER70S-G, ER308L and ER309L deposits were acceptable, regardless of welding parameters. Tensile tests were conducted for both welds according to ASTM A370 requirements, The corrosion resistance of the welds produced by ER309L and ER 308L were relatively higher compared to ER 70S-G. All three specimens exhibited severe attack on the mild steel area, This investigation has shown that ER 309L and ER308L filler metals can be used to join mild steel to stainless steels, but ER 309L is the best due to high tensile strength values.